The effect of nitriding on the fretting wear of a high strength steel at ambient and elevated temperatures - Pearson, Stephen R. (2013)
This work is an experimental evaluation of the wear and friction of a high strength alloy steel (super-CMV (SCMV» in its as heat treated and plasma nitrided states under fretting conditions in air, at both ambient and elevated temperatures.